Pharyngeal dysphagia in inflammatory muscle diseases resulting from impaired suprahyoid musculature - Langdon, Claire; Mulcahy, K.; Shepherd, K.; Low, V.; Mastaglia, F. (Springer New York LLC, 2012)
Dysphagia has previously been reported in the inflammatory myopathies (IMs): inclusion body myositis (IBM), dermatomyositis (DM), and polymyositis (PM). Patients report coughing, choking, and bolus sticking in the pharynx. Myotomy has been the treatment of choice, with variable success reported. We sought to determine underlying causes of dysphagia in IM patients using instrumental evaluation. Eighteen subjects participated in the study: four with DM, six with PM, and eight with IBM. They underwent simultaneous videofluoroscopy and manometry, yielding 214 swallows for analysis regarding function of the upper esophageal sphincter (UES), swallow initiation, hyolaryngeal excursion, and pharyngeal residue. Penetration and aspiration were also recorded. UES failed to relax in two participants. High incidence of pharyngeal dysphagia was noted; 72% of participants demonstrated abnormalities, including delayed swallow initiation (24%), decreased hyolaryngeal excursion (22%), pyriform residue (17%), and penetration (22%). Dysphagia in IM patients appears to be more due to impaired muscle contraction and reduced hyolaryngeal excursion than the often held belief of failed UES relaxation. The distinction between mechanisms causing patients’ dysphagia should be examined, particularly if CP myotomy is being considered as it may be contraindicated for patients with normal UES relaxation. More studies investigating IM patients pre- and post-myotomy are needed.